Pengaruh Metode Ekstraksi Terhadap Persen Rendemen dan Kadar Fenolik Ekstrak Tanaman yang Berpotensi sebagai Antioksidan - Nungky Pawarti; Muhammad Iqbal; Dwi Aulia Ramdini; Citra Yuliyanda (Medula, 2023)
Antioxidants are chemical compounds with various structures that bind free radicals. Antioxidants can inhibit oxidation reactions even at low concentrations. Antioxidant reactions with free radicals also occur in the body. Antioxidants will bind to free radicals and turn them into less reactive compounds so that cells and organs in the body will be protected from oxidative stress which can trigger various diseases. Identification of antioxidants is done by extracting natural plant materials. The methods often used in extraction include maceration, soxhletation, reflux and percolation. Different extraction processes will affect the type and quality of the compounds produced. The factors that influence the success of the extraction are the type of dissolution, the ratio of the amount of solvent, particle size, temperature, time and method of extraction. Secondary metabolite compounds which are thermolabile will experience an increase in levels with increasing temperature. However, the levels of metabolite compounds will decrease with the addition of higher temperatures. Heating helps metabolite compounds that are insoluble at room temperature to be dissolved maximally so that the extraction process can run well. The amount of active substance produced in extraction will affect the percent yield value. The percent yield value is needed to determine the amount of extract produced during the extraction. The yield data also has a close relationship with the active compounds in a sample. The higher the yield value, the more active compounds contained in the sample.